Negotiating research in the shadow of migration control: Access, knowledge and cognitive authority. (1st July 2019) - Rosset, Damian; Achermann, Christin
Abstract : This article recounts the failure to gain access to the Swiss asylum agency's 'country of origin information' (COI) unit and how it negatively impacted access to similar research sites in Europe. As producers of indispensable expert knowledge, these units play an important instrumental and symbolic role in asylum procedures and policies. Interpreted as a situated case of knowledge control, rather than a general resistance to research within the institution, the denial of access reveals how the intended research challenged gatekeepers' idealised construction of COI – both as a type of knowledge and as a field of practice. The negotiation about access gradually shifted to other topics, such as the researcher's competence, the field's situation and the nature of legitimate knowledge – all related to politics of expertise and the COI units' legitimising functions in the wider migration apparatus. The negotiation became a competition over cognitive authority and the monopoly of legitimate knowledge production about the field. By black‐boxing country information, the gatekeepers fostered the illegibility of bureaucratic processes and the legibility of the state as discourse. Analysing the 30‐month negotiation process also reveals the difficulties to seize the contours of the state when encountering transnational bureaucratic fields.